The DSC Index: A new prognostic tool for evaluating functional status in interstitial lung disease - Kchaou, Khouloud; Khaldi, Soumaya; Ben Lazreg, Nadia; Ben Khamsa, Saloua; Masmoudi, Kaouthar (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: The usefulness of the 6-Minute Walk Test (6MWT) in Interstitial Lung Disease (ILD) has been proven. This test assesses the 6-Minute Walk Distance (6MWD), Oxygen Saturation (SpO2) and Chronotropic Response (CR). We aimed to develop an index, the Distance-Saturation-Chronotropic Response (DSC) index and to analyze its relevance in the evaluation of functional capacity and prognosis of patients with ILD.Methods: A retrospective study including 101 ILD patients was conducted. Data collected were results of Pulmonary Functional Tests (PFTs) and 6MWT. We developed a staging system called DSC index and divided it into 3 items (minimal SpO2, 6MWD and CR). Points are assigned to each item ranging from 0 to 2. The scores of each item are summed to obtain the DSC score. The maximal score is 6. To evaluate the reliability of the DSC in assessing functional impact, we analyzed correlations of DSC index with PFTs results and Gender-Age-Physiology (GAP) index. In addition, Receiver Operating Characteristic (ROC) curves were plotted for DSC index and its components, taking a GAP stage ≥ 2 as reference.Results: The DSC index was correlated with respiratory function and GAP score. This correlation was greater than those of PFTs results and GAP score with each component of the DSC taken independently. The ability of DSC to discriminate patients with a GAP stage ≥ 2 was better than that obtained for each 6MWT parameter.Conclusions: The DSC index could be considered a practical tool for global assessment of functional capacity and prognosis in patients with ILD.